Antioxidants activity in pineapple CV. N36 culture under aluminium stress - Aziz, A.; Nurhalim, M.S. (Penerbit Universiti Kebangsaan Malaysia, 2012)
Aluminium is an important stress factor for plants in acidic environments. In the present study, the effect of aluminium-stress on the oxidative enzymes and antioxidant activities in pineapple cv. N36 plantlets was investigated. The plantlets were cultured in MS medium containing 100 μM Al (pH 4.0) for 30 days. Results showed that fresh and dry weight, ascorbic acid content and catalase (CAT) enzyme activity were not significantly (p>0.05) affected by Al-stress. Al did significantly (p<0.05) reduce the α-tocopherol content (2.76 mg/fwt.) and guaiacol peroxidase (GPX) enzyme activity (3.39 units/mg protein), and increased the enzyme ascorbate peroxidase (APX) activity (7.16 units/mg protein). These results indicated that long-term Al-stress did change antioxidant substances content and oxidative enzymes activities in the leaves of pineapple cv. N36 plantlets.